Emerging Treatments and the Clinical Trial Landscape for Hidradenitis Suppurativa-Part II: Procedural and Wound Care Therapies - Natalie M. Fragoso; Rahul Masson; T. Justin Gillenwater; Vivian Y. Shi; Jennifer L. Hsiao (Adis, Springer Healthcare, 2023)
Abstract Procedural treatments are a cornerstone of hidradenitis suppurativa (HS) management. New interventional therapies are being studied as part of the upsurge in HS research and clinical trials. Additionally, draining wounds can impart a significant negative impact on patients' quality of life, requiring daily dressing changes. However, standardized guidelines on how to best manage HS wounds both day-to-day and post-procedure are lacking. In part II of this emerging therapies review, procedural treatments and wound care dressings and devices that are being investigated for HS management are discussed.